Brugia malayi filarial helminth-derived extracellular vesicles suppress antigen presenting cell function and antigen-specific CD4+ T cell responses - Sanku, Gayatri; Ricciardi, Alessandra; Redekar, Neelam R.; Schaughency, Paul; Lack, Justin; Gazzinelli-Guimaraes, Pedro H.; Nutman, Thomas B. (Frontiers in Immunology, 2024)
Live microfilariae (mf) and mf-derived extracellular vesicles (EVs) have been shown to modulate human antigen presenting cell (APC) function, most notably by suppressing the induction of IL-12 (and other pro-inflammatory cytokines) following activation with LPS and interferon-y. To explore further how EVs alter human APC function, we studied the effect of mf and EVs on human elutriated monocyte-derived dendritic cells (DC) following exposure to Mf, mf-derived excretrory/secretory (E/S) products, E/S depleted of EVs through ultracentrifugation and purified EVs. After demonstrating that the measurable responses induced by live mf could be recapitulated by EVs and EV-containing E/S, we next performed RNAseq analysis of human DC following exposure to live mf, EVs, E/S, or EV-depleted E/S. In our analyses of the data for the DC, using a false discovery rate (FDR)<0.05, EV-exposed DC had induced the expression of 212 differentially expressed genes (DEGs) when compared to unexposed DC and 157 when compared to E/S-depleted EVs. These genes were enriched in GO biological processes associated with neutrophil degranulation and 15 DEGs associated with KEGG Lysosome pathways. IPA analysis point to immune dysregulation. We next aimed to understand the intracellular processes altered by EVs and the effect these have on effector T cells. When SARS CoV-2 Membrane-specific CD4+ TCLs were assessed following EV conditioning of autologous DC and activation with the SARS CoV-2-Membrane peptide pool, we found conditioning reduced the frequency of SARS CoV-2 Membrane-specific CD3+ CD4+ CD154+ cells (p=.015). Similarly, EV-conditioning of SARS CoV-2 Membrane-specific CD3+ CD4+ cells induced fewer cell capable of producing IFN-γ (p=.045). Taken together, our data suggest a modulatory role of EVs on APC function that likely leads to defects in T cell effector function.